Association between serum 25-hydroxyvitamin D levels and bone mineral density in normal postmenopausal women - Vasundhara Kamineni; Akkenapally Prasanna Latha; K Ramathulasi (Wolters Kluwer Medknow Publications, 2016)
Aim: This study was conducted with the objective of assessing serum 25-hydroxyvitamin D (25(OH)D) in postmenopausal women (PMW), to detect osteopenia or osteoporosis in PMW and to establish a correlation between serum 25(OH)D levels and bone mineral density (BMD). Materials and Methods: A total of 100 healthy PMW were selected, and a prospective observational study was conducted to correlate the BMD with serum 25(OH)D levels. Their laboratory investigations along with serum 25(OH)D levels were done. Their BMD was assessed with dual-energy X-ray absorptiometry at lumbar spine and neck of femur; T-scores were derived. Correlation analysis was done to investigate the relationship between serum 25(OH)D levels and BMD. Results: The proportion of osteoporosis at the hip was 31.9% in deficient group, 16.1% in insufficient, and 18.2% in sufficient group and at lumbar spine, it was 27.7%, 16.1%, and 22.7%, respectively. Forty-seven percent of PMW had deficient (<20 ng/ml) serum 25(OH)D levels and 31% had insufficiency. T-score at hip in deficient group was −2.05 ± 0.25, and in an insufficient group, it was −1.79 ± 0.13; T-score at lumbar spine was −1.92 ± 0.12 and −1.79 ± 0.12, respectively, but both were not statistically significant. Osteoporosis was seen in 24%, osteopenia in 55% at hip level and 23% and 59% respectively at lumbar spine. There was no association between serum 25(OH)D levels and BMD neither at hip nor at lumbar spine ( P = 0.51 and P = 0.79 respectively). Conclusion: In this study, among our cohort of patients there was no correlation between serum 25(OH)D levels and BMD. However, Vitamin D deficiency coexists with low BMD. Vitamin D insufficiency is a common risk factor for osteoporosis associated with increased bone remodeling and low bone mass.